Pengaruh Shopping Lifestyle dan Fashion Invovement Terhadap Impulse Buying Pada Konsumen Toko Pakaian Tri Collection di Desa Bandar Masilam, Kecamatan Bandar Masilam - Syafitri Wahyuni; Wan Rizca Amelia; Ahmad Rafiki (Universitas Medan Area, 2023)
This study uses quantitative research methods. The population in this study were consumers of the Tri Collection Clothing Store in 2021 as many as 1244. The sampling technique in this study was carried out by distributing questionnaires to 93 respondents. This study uses 2 independent variables, namely shopping lifestyle and fashion involvement and 1 dependent variable, namely Impulse buying. The tool used to test this research is SPSS 22. The results show that the shopping lifestyle variable has a positive and significant effect on impulse buying, as the result of the t test is 2.120 which means t_count t_(table) is 1.661 and the significant value is 1.661. the resulting 0.037 is smaller than 0.05. The fashion involvement variable has a positive and significant effect on impulse buying, as the results of the t-test are 3.211, which means t_count t_(table) is 1.661 and the resulting significance value is 0.002 less than 0.05. Together, shopping lifestyle and fashion involvement have an effect on impulse buying, as the result of f_count f_(table ) which is 7.313 3.10 with a significance value of 0.001 which is smaller than the level of significance of 0.05.